Specjalne strefy ekonomiczne a rozwój regionalny - doświadczenia światowych gospodarek - Hajduga, Piotr (Special economic zones and regional development experience of world economies, 2006)
The above article describes special economic zones and their function within world economy. Special economic zones (SEZ) are an instrument of a state effecting the national economy. The main aim of this paper is to present an important role of special economic zones in the development of regions. In lust part different definitions and functions of SEZs and regional development were discussed. In the second part the author describs special economic zones in the European Union and China and also shows the benefits of their activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 114-124